Means of computerized analysis for detection of program code appropriation - Mohyliak, Taras (Lviv Polytechnic Publishing House, 2016)
Plagiarism is a common problem for educational institutions. Since it is difficult to detect plagiarized work manually, there is a need of an efficient computerized system, which can detect a theft of program code. For academic purposes, the best results usually give algorithms, based on tokens comparison. However, they can give false positive results in cases of similar code structure, despite having different domain and purpose. We propose to introduce weighting coefficients for tokens and calculate code similarity percentage using those coefficients. Our experiment study should confirm the quality improvement of software plagiarism detection.
Keywords: code appropriation; software plagiarism detection; token comparison; weighting coefficients; code similarity